High-level production of pullulan and its biosynthesis regulation in Aureobasidium pullulans BL06 - Chen, Shuyu; Zheng, Hongchen; Gao, Jiaqi; Song, Hui; Bai, Wenqin (Frontiers in Bioengineering and Biotechnology, 2023)
Pullulan has many potential applications in the food, pharmaceutical, cosmetic and environmental industries. However, the yield and molecular properties of pullulan produced by various strains still need to be promoted to fit the application needs. A novel yeast-like strain Aureobasidium pullulans BL06 producing high molecular weight (Mw) pullulan (3.3×106 Da) was isolated and identified in this study. The remarkable Mw of pullulan produced by A. pullulans BL06 was the highest level ever reported thus far. To further regulate the biosynthesis of pullulan in A. pullulans BL06, three gene knockout strains A. pullulans BL06 ΔPMAs, A. pullulans BL06 Δmel, and A. pullulans BL06 ΔPMAsΔmel, were constructed. The results showed that A. pullulans BL06 ΔPMAs could produce 140.2 g/L of moderate Mw (1.3 × 105 Da) pullulan after 120 h of fermentation. The highest yield level of pullulan to date could vastly reduce its production cost and expand its application scope and potential. The application experiments in food preservation showed that the moderate-Mw pullulan obtained in this work could reduce the weight loss of celery cabbages and mangos by 12.5% and 22%, respectively. Thus, the novel strains A. pullulans BL06 and A. pullulans BL06 ΔPMAs possessed unlimited development prospects in pullulan production at various Mw ranges and pullulan applications in multiple fields.